SPATIO-TIME PSYCHOMOTOR REFERENCES OF MOTOR CHARACTERISTICS IN VOLLEYBALL - Rzhanov, A.A.; Akhmatgatin, A.A.; Lebedinsky, V.Yu.; Kharkovskaya, A.G. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determination of the significance and interpretation of the influence of psychomotor spatio-temporal characteristics of volleyball players on the game process, search for ways and methods to effectively form and develop these abilities. Methods and structure of the study. The novelty of the developed methodology for the development of psychomotor spatio-temporal characteristics of volleyball players lies in their effective assessment and selection of training tools that develop the motor capabilities of athletes. The experimental group (EG) trained using the developed methodological tools that form the psychomotor spatial and temporal orientations of volleyball players. The control group (CG) trained according to the program for sports schools. The experiment involved 72 pupils of the Angarsk secondary school, aged 9-13 years. The experiment lasted from September 2019 to September 2021. Results and conclusions. In the course of the study, it was found that in the CG there were no significant changes in the distinctive sensitivity of movements (DSM), and in the EG it was significantly improved. The evaluation of the results of the psychomotor activity of athletes in tests with game techniques, carried out at the end of the experiment, showed significant differences between the groups, characterizing the improvement in the accuracy of performing the EG techniques relative to the CG.